Hydrogen isotope effect on self-organized electron internal transport barrier criticality and role of radial electric field in toroidal plasmas - Kobayashi, T.; Shimizu, A.; Nishiura, M.; Ido, T.; Satake, S.; Tokuzawa, T.; Ii Tsujimura, T.; Nagaoka, K.; Ida, K. (Scientific reports, 2022)
Self-organized structure formation in magnetically confined plasmas is one of the most attractive subjects in modern experimental physics. Nonequilibrium media are known to often exhibit phenomena that cannot be predicted by superposition of linear theories. One representative example of such phenomena is the hydrogen isotope effect in fusion plasmas, where the larger the mass of the hydrogen isotope fuel is the better the plasma confinement becomes, contrary to what simple scaling models anticipate. In this article, threshold condition of a plasma structure formation is shown to have a strong hydrogen isotope effect. To investigate the underlying mechanism of this isotope effect, the electrostatic potential is directly measured by a heavy ion beam probe. It is elucidated that the core electrostatic potential transition occurs with less input power normalized by plasma density in plasmas with larger isotope mass across the structure formation. This observation is suggestive of the isotope effect in the radial electric field structure formation.